Post-Holocaust politics : Britain, the United States & Jewish refugees, 1945-1948 - Kochavi, Arieh J. (Chapel Hill : University of North Carolina Press, 2001)
Between 1945 and 1948, more than a quarter of a million Jews fled countries in Eastern Europe and the Balkans and began filling hastily erected displaced persons camps in Germany and Austria. As one of the victorious Allies, Britain had to help find a solution for the vast majority of these refugees who refused repatriation. Drawing on extensive research in British, American, and Israeli archives, Arieh Kochavi presents a comprehensive analysis of British policy toward Jewish displaced persons and reveals the crucial role the United States played in undermining that policy. Kochavi arg.
Contents -- Illustrations and Maps -- Preface -- Abbreviations and Acronyms -- Introduction -- Part I -- Chapter 1 -- Chapter 2 -- Chapter 3 -- Part II -- Chapter 4 -- Chapter 5 -- Chapter 6 -- Part III -- Chapter 7 -- Chapter 8 -- Chapter 9 -- Part IV -- Chapter 10 -- Chapter 11 -- Conclusion -- Notes -- Bibliography -- Index
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Jewish refugees -- Government policy -- Great Britain; Jewish refugees -- Government policy -- United States; Holocaust survivors -- Europe; Great Britain -- Emigration and immigration -- Government policy; United States -- Emigration and immigration -- Government policy; Jews -- Europe -- Migrations; Palestine -- Emigration and immigration; Réfugiés juifs -- Politique gouvernementale -- Grande-Bretagne.; Réfugiés juifs -- Politique gouvernementale -- États-Unis.; Survivants de l'Holocauste -- Europe; Juifs -- Europe -- Migrations; États-Unis -- Émigration et immigration -- Politique gouvernementale; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; POLITICAL SCIENCE -- Public Policy -- Social Security; Emigration and immigration; Emigration and immigration -- Government policy; Holocaust survivors; Jewish refugees -- Government policy; Jews -- Migrations; Europe; Great Britain; Middle East -- Palestine; United States; Joden; Vluchtelingen; Verenigd Koninkrijk van Groot-Brittannië en Noord-Ierland.; Verenigde Staten; Palestina